العلاقة التكاملية بين الاقتصاد الرقمي والإدارة الرقمية للموارد البشرية - كوار عائشة; العيداني الياس (University of Eloued جامعة الوادي, 2022)
This research paper aims to identify the mutual role between digital human resource management and the digital economy in the organization, by identifying the most important basic concepts about the variables of the study, and it has been concluded that there is an integrated role between electronic management as a form of digital economy and digital human resources management.
The integrative relationship between the digital economy and digital human resource management
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: الاقتصاد الرقمي، الادارة الإلكترونية، وظائف إدارة الموارد البشرية الرقمية; digital economy, electronic management, digital human resource management functions